Energy Penalty of a Single Stage Gas Permeation Process for CO2 Capture in Post-combustion: A Rigorous Parametric Analysis of Temperature, Humidity and Membrane Performances. (July 2017) - Giordano, Lorena; Roizard, Denis; Bounaceur, Roda; Favre, Eric
Abstract: Over the last decade, membrane separation processes have attracted considerable research attention. This is due to their potential for lowering the costs of post-combustion CO2 capture compared with the more established technologies, which are based on the use of chemical solvents. It is well known that the performance of membrane-based CO2 capture is related to several factors, including flue gas composition, membrane material and system design. Membrane working temperature is one of the operating parameters that have several implications on the CO2 separation process. However, surprisingly, this key operating variable has not been investigated in detail. It not only influences the intrinsic membrane properties and the feed composition, but also indirectly affects the energy behavior of the whole capture system. Hence, the resulting outcome cannot be intuitively deduced. This work aims to study the effect of membrane operating temperature on a CO2 capture process, which is operated by means of a single stage unit with feed compression and permeate vacuum pumping. The flue gas from a coal-fired power plant is considered, and the variation in separation performances and energy expenses is evaluated with respect to two types of polymeric membranes, which have different gas separation properties (permeability, selectivity). This study reveals that an increase in the membrane operating temperature negatively affects CO2 permeate purity and power consumption to drive the separation process. In addition, the influence on area requirement is strictly related to the type of membrane material.